The foundations of cultural construction from the perspective of Sura al-Baqara Dialogue is a model - Abdulkhaliq, Abdulmunim; Zebary, Ayad (Humanities Journal of University of Zakho, 2022)
Dialogue is an important foundation for building civilization, and is intended to present words and ideas and exchange them between two parties according to specific controls, and has origins and morals to be taken into account to ensure the success of the dialogue, and not to turn it into disagreement and conflict, and dialogue unites society, strengthens its fork, and reduces its problems towards construction, advancement and progress, and the absence of dialogue leads to the exacerbation of disagreement and the disintegration of society, and this has a negative impact on the civilized activity of the nation. The relationship between different civilizations should be based on acquaintance, cooperation and dialogue, not conflict and clash, and the Qur'an directs Muslims towards dialogue, and in Sura Al Baqara a series of diverse dialogues, each of which includes lessons that Muslims should benefit from in dealing with others.